Computing essentials 2006 - O'Leary, Timothy J. (McGraw-Hill Technology Education, 2006)
The goal of Computing Essentials is to provide students with the basic for understanding the concepts necessary for success in the information age. Computing Essentials also endeavors to instill in students an appreciation for the effect of information technology on people and our environment and to give students a basic for building the necessary skill set to succeed in this new 21st century.